Acute Aortic Dissection with an Aorta–Right Atrium Fistula - Frank, Michael W. (2003)
We describe a rare complication of an acute aortic dissection. Proximally the dissection propagated into the right atrium, resulting in an aorta–right atrium fistula. The clinical course, operative findings, and operative treatment are discussed. (Tex Heart Inst J 2003;30:335–6)